Decision Support System for Determining the Position of Players in a Football Team Using the Simple Multi At Tribute Rating Technique - Simeon Sergius Iyai (Jurnal Mandiri IT, 2021)
One of the keys to a team's victory in a soccer match is about the composition of players or the placement of a player's position in accordance with the abilities he has in the team. In general, the determination process is carried out manually based on the trainer's estimates. In this way, it is impossible to know the value of a formation/team with a certain composition of players. In this study, the authors create a decision support system that can assist the coach in determining the most appropriate players to occupy a position in the team formation. Various assessment factors that become decision variables in this system will be taken into consideration in choosing their position. The assessment factors used are weight (kg), height (m), assessment of tactical assessment techniques, psychological assessment, physical assessment, knowledge of a player who is judged when a player makes attacks, defenses, transitions, scoring per position: goalkeeper, back, center, front. The author uses the Simple Multi Attribute Rating Technique (SMART) method because it is considered the most suitable in this case. By considering various attributes, the value of each player, the value of the player in a formation, and the value of a team formation can be obtained with good results.